Fintech’s Impact on the Digital Transformation of the Qatar Insurance Sector: Opportunities and Challenges (American Journal of Financial Technology and Innovation, 2024)
This study provides a comprehensive analysis of Qatar’s digital insurance industry using a conceptual framework based on established theories. The study aimed to assess different challenges and opportunities, including the regulatory environment, market dynamics, competitive strategies, and digital payment and financial inclusion in Qatar, and also fill a critical gap in the literature. The study uses a positivist perspective and deductive methodology to explore Qatar’s digital insurance sector, revealing diverse demographics and strong correlations between variables like regulations and competitive rivalry, highlighting the positive attitude towards digitization in the industry. The regression model, elucidating 61.7% of the variance, accentuates the pivotal role of “Competitive Rivalry and Enhanced Digital Insurance Sector.” Nevertheless, non-significant contributions from “Security Challenges for Digitization” and “Market Competitiveness” beckon further exploration. The study concludes with insightful recommendations for transparency enhancements, digital tool exploration, and addressing new entrant barriers, offering invaluable guidance to industry stakeholders navigating Qatar’s dynamic digital insurance landscape.